Long‐term follow‐up of patients treated with aminosalicylates for ulcerative colitis: Predictive factors of response: An observational case‐control study. Issue 8 (1st October 2019) - Marti-Aguado, David; Ballester, María Pilar; Tosca, Joan; Bosca-Watts, Marta Maia; Navarro, Pablo; Anton, Rosario; Pascual, Isabel; Mora, Francisco; Minguez, Miguel
Abstract : Background: Knowing patients' ulcerative colitis history is essential to selecting the appropriate therapy according to risk stratification. Objective: To evaluate and identify predictive factors of non‐response to aminosalicylates judged as the need for a step‐up approach over time. Methods: A case‐control study of ulcerative colitis patients treated with aminosalicylates after the diagnosis of disease flare included in the ENEIDA single‐centre registry from 1997 to 2017. Long‐term treatment maintenance with aminosalicylates and higher therapeutic requirements were recorded. The cumulative incidence of treatment escalation was estimated using Kaplan‐Meier curves and compared by the log‐rank test. Cox regression analysis was performed to identify predictive factors of treatment with immunomodulators, biological agents or surgery. Results: A total of 457 patients were included, of whom 28% ( n = 126) were non‐responders to aminosalicylates. The cumulative probability for a step‐up approach within 20 years of follow up was 35%, mainly due to steroid‐dependent colitis. Risk factors for treatment escalation were age ≤27 years (hazard ratio 2.31, 95% confidence interval 1.36–3.92), extensive colitis (hazard ratio 1.65, 95% confidence interval 1.04–2.60), Mayo endoscopic subscore ≥2 (hazard ratio 1.45, 95% confidence interval 1.02–2.06) and extraintestinal manifestations (hazard ratio 2.04, 95% confidence interval 1.03–4.05). Conclusions: Aminosalicylates represent an effective maintenance therapy. Younger age, extensive colitis, endoscopic disease severity and extraintestinal manifestations are risk factors for higher therapeutic requirements.